2012
DOI: 10.1097/pai.0b013e3182233f9f
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Gradient 2 Overexpression in Lung Adenocarcinoma

Abstract: The histologic subtyping of the 2 major histotypes of nonsmall-cell lung cancer, that is, adenocarcinoma (AdC) and squamous cell carcinoma (SCC), is crucial to therapeutic decision making, but making this distinction can be a challenge. Querying the Oncomine database pinpointed anterior gradient 2 (AGR2) as being upregulated in lung AdC. On applying both quantitative real-time polymerase chain reaction and immunohistochemistry, this study tested the reliability of AGR2 status as a histotype-specific marker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Its expression is well recognized in breast, prostate, and colorectal epithelial cells. It has also been reported that AGR2 expression is predominant in adenocarcinoma as compared to squamous cell carcinoma in NSCLC [23]. Because not all primary lesions expressed AGR2, we excluded it from marker for OSNA assay.…”
Section: Discussionmentioning
confidence: 98%
“…Its expression is well recognized in breast, prostate, and colorectal epithelial cells. It has also been reported that AGR2 expression is predominant in adenocarcinoma as compared to squamous cell carcinoma in NSCLC [23]. Because not all primary lesions expressed AGR2, we excluded it from marker for OSNA assay.…”
Section: Discussionmentioning
confidence: 98%
“…Also of interest are AGR2, KRT8, and SFN. AGR2 is a known proto-oncogene recently confirmed to be overexpressed in lung adenocarcinoma (Pizzi et al 2012), and has been shown to promote cell proliferation and migration in several different cancers (Ramachandran et al 2008;Vanderlaag et al 2010;Park et al 2011). KRT8, encoding keratin 8, was previously reported to be up-regulated in lung adenocarcinoma (Wikman et al 2002); and SFN, encoding stratifin, has been reported to be overexpressed in early invasive lung adenocarcinoma (Shiba-Ishii et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis, Long and Hornick [11] demonstrated that 80% of esophageal and 90% of anal squamous cell carcinomas express SOX2, with less than 20% of adenocarcinomas at these sites demonstrating expression. Anterior gradient homolog 2 (AGR2) encodes a 17-kd protein expression of which has been identified in adenocarcinomas of varying sites, including lung, breast, and prostate [12][13][14][15]. We recently identified increased levels of expression of AGR2 in esophageal adenocarcinoma [16].…”
Section: Introductionmentioning
confidence: 97%